2021
DOI: 10.1002/jmor.21431
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the suboccipital region in snakes, and the anatomical and functional diversity of the myodural bridge

Abstract: The myodural bridge, that is, skeletal muscle fibers attaching to the cervical dura mater, has been described from a variety of mammals and other amniotes. To test an earlier assumption about the presence of the myodural bridge in snakes, a comparative study was designed using a group of Colubrine snakes. Serial histological sections revealed no evidence of the myodural bridge in any of the snakes examined. Further analyses, including histology, computed tomography (CT), and micro-CT imaging of other distantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[30] e myodural bridge of Alligator is well-developed, and contraction of the myodural bridge changes the CSF pressure. [39] ere continues to be debate regarding the functional role and significance of the myodural bridge; [12,23] two common hypotheses are that the myodural bridge functions to alter CSF pressure, or that it adjusts/regulates the dura. [13] e results of the present study support both these hypotheses; more specifically, our data suggest that the myodural bridge of Alligator is functioning to regulate the transition in dural compliance at the foramen magnum and that, by doing so, it plays a role in influencing the dynamics of CSF exchange between the cranial and spinal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…[30] e myodural bridge of Alligator is well-developed, and contraction of the myodural bridge changes the CSF pressure. [39] ere continues to be debate regarding the functional role and significance of the myodural bridge; [12,23] two common hypotheses are that the myodural bridge functions to alter CSF pressure, or that it adjusts/regulates the dura. [13] e results of the present study support both these hypotheses; more specifically, our data suggest that the myodural bridge of Alligator is functioning to regulate the transition in dural compliance at the foramen magnum and that, by doing so, it plays a role in influencing the dynamics of CSF exchange between the cranial and spinal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The physical bases for these movement-induced CSF pulsations are not clear. Crocodylians have a well-developed myodural bridge, a link between cervical skeletal muscles and the dura 23 . These suboccipital muscles would likely be contracting during head rotations, and previous experimental studies on alligators have shown that contraction of the myodural bridge alters the CSF dynamics 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Another key difference between manual tail oscillations and the oscillations of the body and head during locomotion, is the potential influence of the myodural bridge. The myodural bridge is a specialization of the suboccipital muscles in which muscle fibers insert onto the dura adjacent to the first cervical vertebra (the atlas) [ 63 ]. Though other functions have been proposed [ 64 ] there is a consensus that the myodural bridge could influence CSF dynamics during turning (oscillating) the head.…”
Section: Discussionmentioning
confidence: 99%